Discrete-time sliding-surface based control of parametrically uncertain nonlinear systems with unknown time-delay and inaccessible switching mode detection - Homaeinezhad, M. R.; Yaqubi, S. (International journal of control, 2021)
This paper focuses on proposing a novel method regarding general tracking control of discrete high-order parametrically uncertain systems with unknown arbitrary switching signals and unknowable time-delay. To this end, a common Lyapunov-Krasovski function (CLKF) is designed based on the sliding hyper-plane featuring individual subsystems in various switching cases. Investigating the proposed function, the necessary conditions for achieving control objectives are obtained in order to ensure stability and finite-time convergence to an invariant set over various modes of an uncertain arbitrary switching signal. Despite constructing the control algorithm for general switched systems, the selection of control signal is based on appropriately calculated input bounds rather than a switching term itself, resulting in no chattering effects in control input. Subsequently, the effectiveness and accuracy of the proposed control method is verified using numerical and experimental examples.